PENGELOLAAN ALOKASI DANA DESA (ADD) DI DESA NAHAAYA KECAMATAN PESOHILIR KABUPATEN BULUNGAN PROVINSI KALIMANTAN UTARA - Noviyanti Noviyanti; Mulyana Mulyana (Program Studi Keuangan Publik, 2017)
AbstractThis research has aim to determine the process of village fund allocation management,the benefit or the barrier factors perceived by the public, as well as how to overcome obstaclesin order to better in the future. This research method used qualitative techniquein accordance with the inductive approach. The results of this study is indicated thatthe village fund allocation management each year in the Nahaaya Village said overallhas been running as expected. It is proved that the funds are used in accordance withproper and appropriate regulations. Although it has been going well of course there isstill found barriers obstacle occurring in the Village Fund Allocation Management forexample due to the lack of human resources qualified caused by their education. The authoralso determine the contributing factors to support the process of village fund allocationmanagement, for example is the cooperation between the government and societyin the development process. Efforts are being made to overcome these obstacles is theaddition of a schedule as well as outreach to rural communities to provide counseling tothe village to see and learn the guidelines given by the Bulungan Regency. In this study,the author suggest that Team Facilities of Village Fund Allocation Program in PesohilirDistrict, Bulungan Regency, should be more effective, efficient, and more thorough indisseminating the Village Fund Allocation to the public. Besides that, good cooperationshould be done by all elements of the program managers Village Fund Allocation Management,both from the Village Government, District Government and Regency Government.And evaluation of various deficiencies in the process of disbursement of funds,which is done in the future to find the right solution for joint comfort.Keywords: management, village, village fund allocation